Krtik Matan Hadis-Hadis Tentang Bid’ah - Dame Siregar (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
Bid'ah is mahdah of worship that is not prescribed, (al-mukhalafatus lissunnah) in the Qur'an described in Surat an-Nur verse 63 with language that is easily understood that (yukholifu 'an amri) meaning that those who violate the Prophet's command. Sentences of al-amru al-muhaddis al-ladzi lam yakun ‘alaihi as-sohabah wa at-tabi’un (the held command that is not practiced by his friend and tabi'in) described in Surah al-Hujurat paragraph 1 the term la tuqoddimu baina yadayil lahi wa rosulih (meaning that you do not precede Allah and His Messenger). That is do not be establish of worship material before coming Qur'an and the hadith decide. Means the companions of Allah's Apostle prohibited from making worship before there are verses and Hadith. In Sura al-Hashr verse 7 (meaning what Messengers given to you, then accept it. And what he forbids you, then leave)